Peran Pemerintah Daerah dalam Pengembangan Pariwisata Pantai Padang Melang di Desa Batu Berapit Kecamatan Jemaja Kabupaten Kepulauan Anambas - Desmayeti Arfa; Junriana; Dwi Aprita (Jurnal Ilmu Sosial dan Ilmu Politik, 2021)
Anambas Islands Regency has the potential for tourism objects that attract foreign and local tourists, one of which is the Padang Melang beach tourist attraction. The existence of the Padang Melang Beach tourist attraction in Batu Berapit Village can have a positive impact on the preservation of the natural environment for the government and the surrounding community in managing and developing the potential of tourism objects by providing information and educational values. The problem that still occurs at the location of the Padang Melang beach area is because the area still lacks coordination in its management so that it does not support the income levy on tourism objects in that location. The purpose of this research is to know the role of local government in the development of Padang Melang beach tourism in Batu Apit Village, Jemaja District, Anambas Islands Regency. This research is descriptive with a qualitative approach. The population in this study is the total number of employees of the Tourism and Culture Office of the Anambas Islands Regency and the entire community in Batu Berapit Village, Jemaja District. This research uses purposive sampling technique. This study uses primary data and secondary data. Data collection techniques in this study are observation and interviews. The data analysis technique used is qualitative data analysis. The results of this study are that the Anambas Regency Government has carried out its role in the development of Padang Melang Beach Tourism in Batu Berapit Village, Jemaja District, Anambas Islands Regency, but it is still not optimal. Suggestions that can be given in this study are that the Anambas Islands Regency Tourism Office must make plans and strategies to attract investors to invest in the Padang Melang Beach tourism area, as well as carry out better management and supervision of the Padang Melang Beach tourist area.